Heat transfer intensification of nanomaterial with involve of swirl flow device concerning entropy generation - Zahir Shah; M. Jafaryar; M. Sheikholeslami; Ikramullah; Poom Kumam (Scientific Reports, 2021)
Abstract The thermal features of hybrid nano-powder turbulent motion through a pipe employing helical turbulator is numerically simulated via Finite Volume Method (FVM). The hybrid nanofluid (MWCNTs + Fe3O4 + H2O) is obtained by uniformly dispersing MWCNTs + Fe3O4 nanomaterials in H2O. The characteristics features of thermal energy transfer of hybrid nanofluid are investigated by varying the pitch ratio (P) of the helical turbulator and Reynolds number (Re) of the fluid. The outputs of the study are depicted in terms of contour plots of temperature, velocity, frictional irreversibility Sgen,f, and thermal irreversibility Sgen,th. The variation of Sgen,f, and Sgen,th with changing P and Re are also displayed by 3D plots. It is found that making the fluid more turbulent by increasing Re, the temperature of the fluid drops whereas the fluid velocity augments. The frictional irreversibility enhances, whereas the thermal irreversibility drops with the increasing turbulent motion. The decreasing P causes to drop the temperature of the higher turbulent fluid flow, while opposite effect is observed for smaller Re. The decreasing P causes to enhance the fluid mixing and thus augments the fluid velocity. Sgen,f and Sgen,th both augment with decreasing P. The comparison of current outputs with the older article shows an acceptable accuracy. The results of the present investigation will be useful in modelling of efficient thermal energy transfer systems.